2014
DOI: 10.1007/s00259-014-2774-y
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG uptake as a prognostic variable in primary differentiated thyroid cancer incidentally detected by PET/CT: a multicentre study

Abstract: An intense (18)F-FDG uptake of the primary DTC is associated with persistence/progression of disease. However, when all other prognostic factors have been taken into account, (18)F-FDG uptake does not add further prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…Fourthly, considering the connection between BRAF V600E mutation and mortality (34) and the inverse correlation between survival and FDG uptake in DTC patients (35,36), we tested the association between primary thyroid tumour uptake (expressed in terms of SUV ratio) and BRAF V600E mutation in vivo; to our knowledge, this was the first such test. Although this association has recently been reported in patients with DTC metastases (37), we did (38); in such cases, a low number of BRAF V600E mutations should be expected a priori, as indeed we found (22%).…”
Section: F-fdg Pet/ct Mpus and 99mmentioning
confidence: 99%
“…Fourthly, considering the connection between BRAF V600E mutation and mortality (34) and the inverse correlation between survival and FDG uptake in DTC patients (35,36), we tested the association between primary thyroid tumour uptake (expressed in terms of SUV ratio) and BRAF V600E mutation in vivo; to our knowledge, this was the first such test. Although this association has recently been reported in patients with DTC metastases (37), we did (38); in such cases, a low number of BRAF V600E mutations should be expected a priori, as indeed we found (22%).…”
Section: F-fdg Pet/ct Mpus and 99mmentioning
confidence: 99%
“…reported on 54 FDG‐avid primary differentiated thyroid carcinoma patients incidentally detected on FDG‐PET/CT. The authors reported that the FDG avidity of the primary differentiated thyroid carcinoma was associated with the persistence or progression of the disease, although, on multivariate analysis, the FDG avidity did not add further prognostic information . Unlike the report of Piccardo et al., our study enrolled both FDG‐avid and non‐FDG‐avid tumors, and we evaluated only PTCs in a larger number of patients, thus enhancing the integrity of our study.…”
Section: Discussionmentioning
confidence: 95%
“…Yun et al [10] reported that visual FDG positivity was associated with central lymph node metastasis, but the SUV of PTMC was not. Recent studies have concluded that FDG uptake did not add further prognostic information [21,22]. Study limitations included that there were a small number of PTC patients and some of them included only PTMC, not large PTC.…”
Section: Discussionmentioning
confidence: 99%